The social economy of new rural reconstruction - Jia'en, Pan; Jie, Du (China Journal of Social Work, 2011)
This paper employs the concept of ‘social economy’ to reflect on the authors' experiences in rural reconstruction efforts in Mainland China, including work on peasant cooperatives and community-supported agriculture. In practice, the social and the economic can never be clearly separated. Economic problems, which may superficially appear to be independent, are in fact over-determined by all kinds of social and cultural factors, so a holistic perspective of ‘social economy’ is needed to re-embed the economic into its social context. Such a perspective can help expand the space of our practice and reflection thereon, in particular helping practitioners to understand the difficulties encountered in rural reconstruction.
Cultural Studies
Keywords: China; new rural reconstruction; perspective; social economy

Neoliberalism as a state-centric class project: The Italian case - Briziarelli, Marco (Continuum: Journal of Media & Cultural Studies, 2011)
This essay sheds light on the neoliberal aspects of the Italian political-economic system exemplified in the relationship between capital, state and media. The main argument is that the specific marriage between neoliberalism and neocorporatism that characterizes Italy reveals a distinctive characteristic of neoliberalism: a class project relying heavily on the state. As Polanyi has suggested through the concept of 'embeddedness', capitalism has consistently developed through the double movement of preaching the independence of the free market from the state and requiring the state's protectionist interventions. After describing this state-centric framework to interpret neoliberalism, in the second part of the paper, I consider the political-economic history of Italy's recent decades, paying particular attention to the media system. I will examine the 'communicative performance' of neoliberalism in Berlusconi's discourses and concrete political decisions taken in the name of neoliberalism. The articulated relationship between media and politics reveals the continuous attempts by the advocates of neoliberalism to seize the state, not to reduce its intervention but in fact to manipulate the market.
Communication Studies; Media Studies; Cultural Studies
Keywords: Italy; economic indicators; essays; mass media audiences; neoliberalism; political economic analysis